2023
DOI: 10.2174/1389557523666230202103719
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Morita-Baylis-Hillman Adducts (MBHA)

Abstract: Background: The Morita-Baylis-Hillman reaction (MBHR) is considered one of the most powerful and versatile methodologies used for carbon-carbon bond formation. The reaction is defined as the condensation between an electrophilic carbon sp² and the α position of an olefin, carrying an electron-withdrawing group, in the presence of a catalyst. The advantages of the reaction are the high atom economy and mild reaction conditions. Under ideal conditions, this reaction leads to the formation of multifunctional prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 104 publications
2
6
0
Order By: Relevance
“…The second H1b hypothesis established for the development of this study presumes that there is a positive relationship between the business environment and subjective norms, in which the findings support the acceptance of H1b. This result is consistent with Kobylińska [9], Choudhury and Mandal [21], Georgescu and Herman [22], Gieure et al [15], Krüger et al [38], and Paiva et al [39] when noting that the influence of family, friends and contact with successful people in business are crucial for the motivation and involvement of higher education students in business projects. This allows to say that an important predictor of university students' entrepreneurial intentions is the business environment that should be "attractive for students to think about startups" [21] (p. 2).…”
Section: It Is Acceptedsupporting
confidence: 89%
See 3 more Smart Citations
“…The second H1b hypothesis established for the development of this study presumes that there is a positive relationship between the business environment and subjective norms, in which the findings support the acceptance of H1b. This result is consistent with Kobylińska [9], Choudhury and Mandal [21], Georgescu and Herman [22], Gieure et al [15], Krüger et al [38], and Paiva et al [39] when noting that the influence of family, friends and contact with successful people in business are crucial for the motivation and involvement of higher education students in business projects. This allows to say that an important predictor of university students' entrepreneurial intentions is the business environment that should be "attractive for students to think about startups" [21] (p. 2).…”
Section: It Is Acceptedsupporting
confidence: 89%
“…Other recent studies such as those by Gieure et al [15], Georgescu and Herman [22], Krüger et al [38], and Kobylińska [9] also reported that subjective norms and family context are predictive of students' intention to become entrepreneurs after graduation. Hence, Paiva et al [39] found the influence of the family context on the entrepreneurial intention of Brazilian and Portuguese university students. Additionally, they identified that more men than women intend to create businesses after graduation.…”
Section: H1a: There Is a Positive Relationship Between Education (Edu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Trivalent chromium, Cr(III), exists as cationic species (Cr 3+ , Cr(OH) 2+ , Cr(OH) 2 + ) [6] and has been considered as an essential nutrient involved in the regulation of glucose [33,34], due to its participation in the activation of an insulin receptor [35,36]. It can be frequently found in the form of chromium picolinate in dietary supplements.…”
Section: Chemistry Of Chromiummentioning
confidence: 99%